2001
DOI: 10.1074/jbc.m101676200
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin Affects β-Catenin-associated Pathways

Abstract: Calreticulin, a Ca2؉ storage protein and chaperone in the endoplasmic reticulum, also modulates cell adhesiveness. Overexpression of calreticulin correlates with (i) increased cell adhesiveness, (ii) increased expression of N-cadherin and vinculin, and (iii) decreased protein phosphorylation on tyrosine. Among proteins that are dephosphorylated in cells that overexpress calreticulin is ␤-catenin, a structural component of cadherindependent adhesion complexes, a member of the armadillo family of proteins and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 66 publications
3
45
0
Order By: Relevance
“…19,20 Cells underexpressing CRT have increased expression of calmodulin, activated CAMKII (calmodulin-dependent kinase II), and c-src, causing weak adhesion and spreading via focal contacts. 18,20,82 Furthermore, CRT null mouse embryo fibroblasts demonstrate decreased ability to migrate on fibronectin and laminin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 Cells underexpressing CRT have increased expression of calmodulin, activated CAMKII (calmodulin-dependent kinase II), and c-src, causing weak adhesion and spreading via focal contacts. 18,20,82 Furthermore, CRT null mouse embryo fibroblasts demonstrate decreased ability to migrate on fibronectin and laminin.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Cells underexpressing CRT have increased expression of calmodulin, activated CAMKII (calmodulin-dependent kinase II), and c-src, causing weak adhesion and spreading via focal contacts. 18,20,82 Furthermore, CRT null mouse embryo fibroblasts demonstrate decreased ability to migrate on fibronectin and laminin. 17 Whereas GFP-CRT expression was not localized to focal contacts, one study shows that CRT and another ER-resident protein, RAP (low-density LRP receptor-associated protein) are associated with integrin-based cellular adhesion complexes that link to the cytoskeleton, containing such signaling proteins as vinculin, talin, paxillin, focal adhesion kinase, and ␣-actinin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that CRT expression levels can modulate intracellular signaling, including the ␤-catenin pathway, by altering protein-tyrosine kinase or phosphatases (40). It was observed that overexpression of CRT in mouse L fibroblasts decreased protein phosphorylation at tyrosine and also that the dephosphorylated protein was ␤-catenin, although the mechanism of the CRT-dependent modulation of tyrosine dephosphorylation was not made clear.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of adhesions universally share the cytoskeletal protein, vinculin [5], expression of which is affected by the level of calreticulin expression [6,7]. Changes in the level of calreticulin expression also affect expression of the intercellular junction protein, N-cadherin [8]. It is unclear whether the effects of calreticulin on cellular adhesiveness are mediated by its role in Ca 2+ -homeostasis or by its chaperone function.…”
Section: Introductionmentioning
confidence: 99%